Injury trends in Pencak Silat: Impact of regulation changes on sparring athletes - Jhenny Ayu Suryaningrum; Mohamad Nizam Mohamed Shapie (CV Rezki Media, 2025)
Background: Pencak Silat is a martial arts sport with high physical contact intensity, resulting in a high risk of injury. To improve safety and sportsmanship, PERSILAT changed the competition rules in 2017. However, the impact of these changes on athlete injury rates is still debated. Objectives: This study aimed to compare injury rates between the old and new rules in the sparring category of Pencak Silat athletes. Methods: The study involved 40 sparring category Pencak Silat athletes in the Greater Malang area, aged 16-25 years, who had experience competing before and after implementing the new rules. Sampling used a purposive sampling technique. Data were collected through an online questionnaire and analyzed descriptively quantitatively with percentage calculations. Results: The results showed a decrease in injury rates in the new rules compared to the old rules. 50.00% of respondents were injured 1-2 times under the new regulation, lower than 57.50% under the old regulation. The most common injury was bruising (27.06% under the new rules vs. 36.36% under the old rules), while dislocation injuries increased (18.82% vs. 15.58%). The most common injury was to the ankle. Most athletes stated that injuries affected their performance and daily activities. Conclusions: Rule changes have not eliminated the risk of injury in high-contact sports such as Pencak Silat. A decrease in bruising followed by increased dislocations suggests the need for more specific prevention strategies. This study contributes to understanding the impact of new regulations on athlete safety.